THE EFFECT OF CINNAMON BARK (Cinnamomum burmanni) SUBMISSION ON THE QUALITY OF SMOKED EEL (Monopterus albus) DURING THE STORAGE - Muhammad Cholik Indriyanto; Dewita Buchari; Tjipto Leksono (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
This research aims to see the effect of cinnamon bark submission on the quality of smoked eel during the storage. The method used in this research is experimental method. A random block design was implemented with three different treatments, they were: K0 (without cinnamon solution), K10 (with 10% of cinnamon solution), K20 (with 20% of cinnamon solution) added with salt as much as 2.5% in 30 minutes. They were kept in the room temperature for 28 days and with observation in day 0, day 7, day 14, day 21, and day 28, so the experiment unit was 3x5=15 times. The parameter examined was organoleptic (appearance, texture, aroma, taste) and chemical test (water, fat, peroxide number) along with microbiology test (total mold colonies). The result of this research showed that by soaking the cinnamon bark submission, it did not give significant effect on the appearance, taste, and texture with the accuracy level 95%. On the other hand, it gave significant effect on the chemical test (peroxide number test) and microbiology test (total mold colonies) with the accuracy level 95%. The submission of 10% cinnamon solution was the best treatment of all as its smoked eel quality had bright and shiny color. Until the final day of the storage or in day 28, those three kinds of smoked eel products were not overgrown by mushroom.Key Words: cinnamon bark, eel, smoke liquid